Design and Implementation of Camera Capture Control Using Voice Command and Internet of Things (IoT) - Heru, Heru Susanto (ReTII, 2019)
Image capture using camera is still mostly done through hardware contact with a limited distance. The development of voice recognition technology and the Internet of Things, control of image capture using camera can be done with voice commands without making hardware contacts and remotely. This paper aims to explain the design and implementation of camera capture controllers using voice commands and internet of things (IoT). The hardware of the system uses NodeMCU + ESP8266, SDCard module, VC0706 serial camera, Arduino Mega 2560, and Google Assistance. The software of the system uses Arduino IDE, Adafruit application and IFTTT (If This Than That) application. The voice command given will be accepted by Google Assistance and forwarded to the IFTTT application, with Applet is created on the IFTTT then the voice command will be translated to make a command to the Adafruit application in the form switch ON. Adafruit that is connected to the IoT NodeMCU device provides a signal to start capturing the VC0706 camera images connected to the Arduino Mega and the captured images are stored on the SD card. The results of the system implementation have shown that there is an image capture function with the camera running as desired and the results are capturing images stored on the SD card and can be accessed at any time.